Feminisme dalam Kajian Ilmu Filsafat - Srimawati, Nurmawan (Yayasan Sembilan Pemuda Indonesia, 2024)
Feminism theory is a movement that developed since the 19th century and continued to grow in popularity until the 20th century. In general, it can be separated into four periods of improvement: early women's liberation, first wave women's rights, second wave women's liberation, and women's liberation. third wave, or what is called postfeminism. Charles Fourier was a French socialist thinker and founder of the concept of feminism in 1837. Charles Fourier's mission was to free humans, men and women, from frustration and depression. Implementation did not go as smoothly as planned, not only because the management approach was relatively new, but also because the conditions and process of adaptation as well as the process of forming a new culture in schools require a relatively long time. Based on our experience, there are several shortcomings and weaknesses that cause MPMBS to be less than optimal. However, the results of this program show that more schools are successful than unsuccessful or unsuccessful schools. Therefore, continuing with Law of the Republic of Indonesia No. Law Number 20 of 2003 concerning the National Education System (Article 51) regulates that the management of early childhood, primary and secondary education units is based on minimum service standards with management principles based on school. In general, it can be partitioned into four. Overall, it can very well be separated into four periods. Women's thinking reflects demands for social improvement that demand equality. Women's liberation is a system of thought and inquiry into public activities and humanitarian experiences that have been created over the long term.